Spleen lymphocyte function modulated by a cocoa-enriched diet (2007)
Previous studies have shown the down?regulating in vitro effect of cocoa flavonoids on lymphocyte and macrophage activation. In the present paper, we report the capacity of a long?term rich cocoa diet to modulate macrophage cytokine secretion and lymphocyte function in young rats. Weaned rats received natural cocoa (4% or 10% food intake), containing 32?mg flavonoids/g, for 3?weeks. Spleen immune function was then evaluated through the analysis of lymphocyte composition, their proliferative response and their ability to secrete cytokines and Ig. In addition, the status of activated peritoneal macrophages was established through tumour necrosis factor (TNF)?? secretion. The richest cocoa diet (10%) caused a reduction of TNF?? secretion by peritoneal macrophages showing anti?inflammatory activity. Similarly, although a 10% cocoa diet increased lymphocyte proliferation rate, it down?regulated T helper 2 (Th2)?related cytokines and decreased Ig secretion. These changes were accompanied by an increase in spleen B cell proportion and a decrease in Th cell percentage. In summary, these results demonstrate the functional activity of a cocoa?high dosage in down?regulating the immune response that might be beneficial in hypersensitivity and autoimmunity.